Impacts of Specific Incivilities on Responses to Crime and Local Commitment, 1979-1994: (Atlanta, Baltimore, Chicago, Minneapolis-St. Paul, and Seattle) - Taylor, Ralph B. ([Verlag nicht ermittelbar], 1998)
This data collection was designed to test the "incivilities thesis": that incivilities such as extant neighborhood physical conditions of disrepair or abandonment and troubling street behaviors contribute to residents' concerns for personal safety and their desire to leave their neighborhood. The collection examines between-individual versus between-neighborhood and between-city differences with respect to fear of crime and neighborhood commitment and also explores whether some perceived incivilities are more relevant to these outcomes than others. The data represent a secondary analysis of five ICPSR collections: (1) CHARACTERISTICS OF HIGH AND LOW CRIME NEIGHBORHOODS IN ATLANTA, 1980 (ICPSR 7951), (2) CRIME CHANGES IN BALTIMORE, 1970-1994 (ICPSR 2352), (3) CITIZEN PARTICIPATION AND COMMUNITY CRIME PREVENTION, 1979: CHICAGO METROPOLITAN AREA SURVEY (ICPSR 8086), (4) CRIME, FEAR, AND CONTROL IN NEIGHBORHOOD COMMERCIAL CENTERS: MINNEAPOLIS AND ST. PAUL, 1970-1982 (ICPSR 8167), and (5) TESTING THEORIES OF CRIMINALITY AND VICTIMIZATION IN SEATTLE, 1960-1990 (ICPSR 9741). Part 1, Survey Data, is an individual-level file that contains measures of residents' fear of victimization, avoidance of dangerous places, self-protection, neighborhood satisfaction, perceived incivilities (presence of litter, abandoned buildings, vandalism, and teens congregating), and demographic variables such as sex, age, and education. Part 2, Neighborhood Data, contains crime data and demographic variables from Part 1 aggregated to the neighborhood level, including percentage of the neighborhood that was African-American, gender percentages, average age and educational attainment of residents, average household size and length of residence, and information on home ownership.